A qualitative study exploring nursing home nurses' experiences of training in person centred dementia care on burnout. (March 2020) - Smythe, Analisa; Jenkins, Catharine; Galant-Miecznikowska, Magdalena; Dyer, Jane; Downs, Murna; Bentham, Peter; Oyebode, Jan
Highlights: This study investigates the impact of training to reduce to reduce burnout in nursing home nurses. The interviews were used to gain insights into the impact of the intervention. Working long hours, feeling overloaded, unsupported, isolated, and not feeling valued all led to nurses' burnout. The training appeared to reverse or break through some of the conditions that led to burnout. Findings demonstrate that training can support nurses working in nursing homes.